School Readiness of Children Exposed to Family and Domestic Violence - Orr, Carolyn (Journal of interpersonal violence, 2022)
Children have a universal right to live free from exposure to family and domestic violence (FDV). Children exposed to FDV can experience long-term effects on their physical and psychological health and their social competencies including social, emotional, and cognitive skills and behaviours that underpin successful social adaptation and academic achievement. The aim of this study was to investigate if children exposed to FDV were more likely to be vulnerable on school readiness measures compared to those children who were not exposed. Our cohort study used de-identified individual-level administrative data of children born during 2002?2010, in Western Australia, who were identified in police and hospital records as being exposed to FDV during 2002?2015. Univariate and multivariate logistic regression was used to estimate the odds of vulnerability in Australian Early Development Census (AEDC) outcomes of children exposed to FDV compared to a non-exposed cohort. After adjusting for demographic characteristics, children exposed to FDV had higher odds than non-exposed children of being vulnerable in all five AEDC domains: physical health and wellbeing, social competence, emotional maturity, language and cognitive skills (school-based) and communication skills and general knowledge. Exposed children have an increased likelihood of vulnerability in all five AEDC domains: physical health and wellbeing, social competence, emotional maturity, language and cognitive skills (school-based) and communication skills and general knowledge. Comprehensive multiagency early intervention for children exposed to FDV is required to mitigate the impact on outcomes, and ultimately the need to prevent FDV is needed.